Syria after the Russian intervention: Moscow tips the military balance in favor of the regime, pursues parallel diplomacy - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2016)
Russian airstrikes turned the tide of the conflict in favor of the regime of Bashar al Assad. Moscow announced a reduction in its military presence in Syria in March 2016 but has maintained its infrastructure in the country while continuing to build up Assad's forces. The cessation of hostilities achieved through a deal between the United States and Russia has lessened the number of attacks against civilians and curbed fighting, but rebel areas remain under siege. At the same time, Russia has been keen to display its interest in an international, cooperative solution. Regard-less of whether Moscow's intentions are sincere or mere lip service, the peace talks underway in Geneva, could provide Germany and the European Union with means to bolster the ceasefire. They should push for a solution that curbs the security sector and other tools of repression, which are dominated by Assad's Alawite minority, rather than for a mere change of personnel at the leadership level. Without such substantial change, the dynamics prompting the influx of refugees is unlikely to change substantially. (SWP Comments)
Keywords: 320